2019
DOI: 10.11646/zootaxa.4691.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Description of two new species of Progonyleptoidellus (Opiliones: Gonyleptidae), with a cladistic analysis of the genus, an overview of relationships in the K92 group, and taxonomic notes on Deltaspidium

Abstract: As part of an ongoing revision and cladistic analysis of the “K92 clade” (Gonyleptidae), the Brazilian genus Progonyleptoidellus Piza, 1940 is revised and two new species from São Paulo State are described: P. bocaina sp. nov. and P. picinguaba sp. nov. A cladistic analysis of the genus was performed using these two new species plus the three previously described species of the genus [P. fuscopictus (B. Soares, 1942); P. orguensis (Soares & Soares, 1954); and P. striatus (Roewer, 1913)], and 25 more additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 854 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Our results also show a close relationship between Neosadocus and other Progonyleptoidellinae species, especially Iguapeia melanocephala and Iporangaia pustulosa . This proximity had been previously hypothesized by Pinto-da-Rocha et al (2014) [42] and Benedetti & Pinto-da-Rocha (2019) [54], also based on molecular data. Caetano & Machado (2013) [75] also suggested that Neosadocus and Progonyleptoidellinae are closely related, based on behavioral, chemical and ecological data.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our results also show a close relationship between Neosadocus and other Progonyleptoidellinae species, especially Iguapeia melanocephala and Iporangaia pustulosa . This proximity had been previously hypothesized by Pinto-da-Rocha et al (2014) [42] and Benedetti & Pinto-da-Rocha (2019) [54], also based on molecular data. Caetano & Machado (2013) [75] also suggested that Neosadocus and Progonyleptoidellinae are closely related, based on behavioral, chemical and ecological data.…”
Section: Discussionsupporting
confidence: 71%
“…Neosadocus Mello-Leitão, 1926: 378 [13]; Kury, 2003: 134 (complete citation listing until 2003) [2]; Machado et al, 2004: 1, 3, 5, 6, 7, 9, figs 2–2b, 11, 14, 18, 19 [51]; Willemart et al, 2007: 40, 41, fig 1, 42, fig 3, 43, fig 4, 44, figs 5 and 7, 46, 47, figs 11–12, 48, figs 13–17, 50, 51, figs 25–27, 52 [52]; Coronato-Ribeiro et al, 2013: 505 [53]; Pinto-da-Rocha et al, 2014: 527 [42]; Benedetti & Pinto-da-Rocha, 2019: 487 [54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neosadocus Mello-Leitão, 1926: 355, 378 [ 13 ] (key; diag; dist); Kury, 2003: 134 (complete citation list until 2003) [ 2 ] (cat); Machado et al, 2004: 1, 3, 5, 6, 7, 9, figs 2–2b, 11, 14, 18, 19 [ 55 ] (biol); Willemart et al, 2007: 40, 41, fig 1, 42, fig 3, 43, fig 4, 44, figs 5 and 7, 46, 47, figs 11–12, 48, figs 13–17, 50, 51, figs 25–27, 52 [ 56 ] (biol); Coronato-Ribeiro et al, 2013: 505 [ 57 ] (cat); Pinto-da-Rocha et al, 2014: 527 [ 46 ] (syst); Benedetti & Pinto-da-Rocha, 2019: 487 [ 58 ] (mat; syst); Kury et al 2020: 35 [ 19 ] (cat). Type species : Sadocus bufo Mello-Leitão, 1923, by original designation.…”
Section: Resultsmentioning
confidence: 99%
“…Neosadocus maximus : Kury, 1995: 205 [ 18 ] (diag; dist); 2003: 135 [ 2 ] (cat); Osses et al, 2008: 519, 520, 522, figs 1–2, 523, figs 4–5, 524, 525 [ 9 ] (biol); Willemart et al, 2009: 52, 53, 54, figs 1–2, 55, figs 3–4, 56, fig 5, 57, 58 [ 10 ] (biol); Rocha et al, 2011: 658, 659, 660, fig 4, 661, figs 5–5b [ 67 ] (biol); Resende et al, 2012: 101, 102 [ 6 ] (cit); Chelini & Machado, 2012: 1620, fig 1, 1621, 1622, 1623, fig 2, 1624, fig 3, 1625, 1626 [ 12 ] (biol); 2014: 1148, 1149, 1150, fig 1, 1151, fig 2, 1152 [ 68 ] (biol); Buzatto & Machado, 2014: 4 [ 69 ] (cit); Buzatto et al, 2014: 1681 [ 70 ] (biol; cit); Pinto-da-Rocha et al, 2014: 522, 534 [ 46 ] (syst); Benedetti & Pinto-da-Rocha, 2019: 462, 466, 467, 468, 469, 470 [ 58 ] (mat; syst).…”
Section: Resultsmentioning
confidence: 99%